Unlocking digital growth: overcoming barriers to digital transformation for Indian food SMEs - Gupta, Sumit; Jagtap, Sandeep (Springer, 2024)
This paper aims to study how firms must be agile to overcome risks and manage cost repercussions. Specifically, it focuses on promoting digitalization in Indian food SMEs for greater competitiveness. The main purpose is to design a model for implementing robust interventions in a rational manner. To achieve this, a mixed approach, including a literature review and the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method, was chosen. This approach is recommended for addressing barriers to digital transformation in SMEs. The results suggest that the absence of internet connectivity and problems related to organization impede the efficiency of operations in small and medium-sized Indian food businesses. By overcoming these obstacles and allocating resources to enhance their digital capacities, stakeholders can effectively shape their future business operations. In addition, it is imperative for the stakeholders to actively adopt and utilize a range of digital tools such as blockchain, IoT, Big Data, and cloud computing. To implement and sustain digital transformation effectively, three foundational elements are crucial: internet availability, financial resources, and employee training. This research offers an innovative approach to the practiceners and mangers to adopt digital transformation of Indian food SMEs.
Keywords: 46 Information and Computing Sciences; 4609 Information Systems; 35 Commerce, Management, Tourism and Services; Digital transformation; Indian food SMEs; Digitalization; Operational productivity; Food sector